Odpowiedź :
Odpowiedź:
a) (3a+4)(7+b) = 21a + 3ab +28 + 4b
b) (2a - b)(2b - 5) = 4ab - 10a - [tex]2b^{2}[/tex] - 5b
c) (-2x)(3x+2y) = [tex]-6x^{2}[/tex] - 4xy
d) (x-xy)(3xy+5x) = [tex]3x^{2} y[/tex] + [tex]5x^{2}[/tex] - [tex]3x^{2} y^{2}[/tex] - [tex]5x^{2} y[/tex] = [tex]-3x^{2} y^{2}[/tex]-2[tex]x^{2} y[/tex] + 5[tex]x^{2}[/tex]
Szczegółowe wyjaśnienie:
Odpowiedź:
[tex]a)\ \ (3a+4)(7+b)=21a+3ab+28+4b\\\\b)\ \ (2a-b)(2b-5)=4ab-10a-2b^2+5b\\\\c)\ \ (-2x)(3x+2y)=-6x^2-4xy\\\\d)\ \ (x-xy)(3xy+5x)=3x^2y+5x^2-3x^2y^2-5x^2y=-2x^2y+5x-3x^2y^2[/tex]